Comparison of isothermal kinetic models during lead adsorption by Azolla caroliniana - Romero-Bonilla, Hugo (2022)
Water contaminated by heavy metals is a risk to public health. This is the reason behind widespread research on water treatment oriented to removing metal ions. This research determined the intensity of adsorption of lead (Pb) by the Azolla caroliniana fern and its capacity to remove lead in synthetic waters. An atomic absorption spectrophotometer was used to determine the concentration of adsorbed lead. Langmuir isotherm graphs showed that the type of isothermal system was unfavorable for the four reactors used in the study (RL's greater than 1). On the other hand, Freundlich isotherm graphs showed the linear models of the kinetic behavior of lead adsorption by Azolla caroliniana for the four reactors and enabled us to determine that the best R2 and the highest adsorption intensity (n) of Pb (0,122) was achieved with reactor D (30 ppm Pb).